Cystathionine β-Lyase-Like Protein with Pyridoxal Binding Domain Characterized in Leishmania major by Comparative Sequence Analysis and Homology Modelling. (17th July 2013) - Negi, Arvind; Bhushan, Satej; Gupta, Pawan; Garg, Prabha; Kumar, Raj
Abstract : Cystathionine β -lyase-like protein (CBLP), one of the key enzymes involved in methionine biosynthesis utilising pyridoxal phosphate (PLP) as a cofactor, has recently been reported in Leishmania major . Its presence in the parasite and absence in humans warrant its full characterisation and fruition as a potent, selective, and inevitable druggable target. Due to the unavailability of X-ray 3D structure of CBLP, a homology model for this protein was developed for the first time. The model was evaluated for PLP binding site and various conserve domain residues of the protein recommended by comparative sequence analyses by different protein analysis tools. The model was validated and discovered to be robust and statistically significant. The final model was superimposed on template of Arabidopsis thaliana (PDB ID: 1IBJ) and RMSD was found to be 0.486. The PLP binding site residues of both the proteins were ensued to be highly conserved indicated by Gly71, Met72, Tyr95, Asp169, and Ser193 as well as formation of aldimine bond with Lys194. This was further verified through molecular simulation of PLP into the cofactor binding site of the modelled protein. The present study may therefore play a directing role in the designing of novel, potential, and selective antileishmanial agents.